A review of common immunotherapy and nano immunotherapy for acute myeloid leukemia - Wang, Yaoyao; Yang, Xiancong; Liu, Yalin; Li, Youjie (Frontiers in Immunology, 2025)
Acute myeloid leukemia (AML) is a highly aggressive hematological malignancy. Traditional chemotherapy methods not only bring serious side effects, but also lead to high recurrence rate and drug resistance in some patients. However, as an emerging therapeutic strategy, immunotherapy has shown great potential in the field of AML treatment in recent years. At present, common immunotherapy methods for AML include monoclonal antibodies, CAR-T cell therapy, and immune checkpoint inhibitors. With the deepening of research and technological progress, especially the application of nanotechnology in medicine, new immunotherapy is expected to become one of the important means for the treatment of acute myeloid leukemia in the future.